2017
DOI: 10.4172/2157-7463.1000333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity and pH on Fatty Acid Profile of The Green Algae Tetraselmis suecica

Abstract: In this study, the marine alga Tetraselmis suecica was cultured in F/2 medium with various rang of salinity and pH. The influence of stressed algal cells to produce biofuels was studied. The neutral lipid (triacylglycerol) assembled by T. suecica was determined using Nile Red dye under salinity stress (up to 1 M NaCl) and pH (pH 7 to 9). Salinity showed a stimulating effect on triacylglycerol in the algal cells at the 1 Molars, while the effect of pH was changeable. Then fatty acid profile of T. suecica cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
7
0
3
Order By: Relevance
“…Thus, pH is not simply a static factor that affects growth, but rather is also an indicator for healthy algal growth. Thus, the natural decline in acid reaction of the algal growth medium gives rise to a decline in algal growth, indicating a high death rate ( Al-Mutairi and Toulibah, 2017 ). In the present study, it was found that the lowest growth occurred at the highest salt level (1.0 M) at all tested pH levels, and that increasing of salt concentration above 0.4 M reduced the dry weight accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, pH is not simply a static factor that affects growth, but rather is also an indicator for healthy algal growth. Thus, the natural decline in acid reaction of the algal growth medium gives rise to a decline in algal growth, indicating a high death rate ( Al-Mutairi and Toulibah, 2017 ). In the present study, it was found that the lowest growth occurred at the highest salt level (1.0 M) at all tested pH levels, and that increasing of salt concentration above 0.4 M reduced the dry weight accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Variasi pH dalam media kultur dapat mempengaruhi metabolisme dan pertumbuhan kultur mikroalga antara lain mengubah keseimbangan karbon anorganik, mengubah ketersediaan nutrien dan mempengaruhi fisiologi sel [8], [10] . Kisaran pH untuk pertumbuhan pada kebanyakan mikroalga antara 7-9 [11] .…”
Section: Padaunclassified
“…Pada hari ke-10 dilakukan variasi pH yaitu pada pH 5, 7, 9, dan pH 8,2 yang merupakan pH pupuk GrowMore 32-10-10. Pemberian variasi pH dilakukan dengan cara menambahkan HCl 10 M untuk suasana asam dan KOH 1 M untuk suasana basa sebanyak beberapa tetes hingga mencapai pH yang diinginkan [8] .…”
Section: Induksi Mikroalga C Vulgaris Dengan Variasi Phunclassified
See 1 more Smart Citation
“…Water bodies with naturally high levels of salinity are widely distributed on all continents of the globe and are the objects of numerous scientific studies (Heidelberg et al, 2013;Afonina & Tashlykova, 2016). The increased attention paid to saline waterbodies is primarily due to the development of specific biota in them, represented by halotolerant and halophilic species, many of which are of biotechnological importance as producers of biologically active substances (Solovchenko et al, 2015;Mohammadi et al, 2015;Almutairi & Toulibah, 2017).…”
Section: Introductionmentioning
confidence: 99%